The Future of Invasion Science Needs Physiology. (5th October 2022) - Boardman, Leigh; Lockwood, Julie L; Angilletta, Michael J; Krause, Jesse S; Lau, Jennifer A; Loik, Michael E; Simberloff, Daniel; Thawley, Christopher J; Meyerson, Laura A
Abstract: Incorporating physiology into models of population dynamics will improve our understanding of how and why invasions succeed and cause ecological impacts, whereas others fail or remain innocuous. Targeting both organismal physiologists and invasion scientists, we detail how physiological processes affect every invasion stage, for both plants and animals, and how physiological data can be better used for studying the spatial dynamics and ecological effects of invasive species. We suggest six steps to quantify the physiological functions related to demography of nonnative species: justifying physiological traits of interest, determining ecologically appropriate time frames, identifying relevant abiotic variables, designing experimental treatments that capture covariation between abiotic variables, measuring physiological responses to these abiotic variables, and fitting statistical models to the data. We also provide brief guidance on approaches to modeling invasions. Finally, we emphasize the benefits of integrating research between communities of physiologists and invasion scientists.